Impact of pressure on surface roughness and kerf characteristics using low pressure abrasive water jet cutting - Nazrin, Mokhtar; Syed, Qutaba; Asmelash, Mebrahitom Asmelash; Mohd Azmir, Mohd Azhari (Pleiades Publishing, 2024)
Abrasive water jet (AWJ) cutting is an emerging material processing technology with significant advantages, such as no thermal deformation, high processing versatility, high flexibility, and low cutting force. It is used in various applications including machining, cleaning, surface preparation, and material cutting. The main concerns during the AWJ cutting process are the surface roughness and the kerf geometry. This study aimed to successfully predict the surface roughness and the kerf geometry during low pressure AWJ machining to cut metal sheets at low and high water pressures when cutting the stainless steel and copper specimens. The experimental results show that a low water pressure indicates fewer variations between the surface roughness and the kerf angle. At various pressures, the roughness values ranged from 3.087 to 4.817 μm. A regression model was developed to predict the surface roughness and the kerf angle. As a result, the effect of water pressure can only increase the kinetic energy but cannot affect other processing parameters separately. Scanning electron microscopy revealed micro-cracks during the AWJ cutting process.